An improvement to the Kalos' formula for double layer gamma ray exposure buildup factors for shielding materials of nuclear and radiological facilities. (February 2021) - Basu, Pew; Sarangapani, R.; Venkatraman, B.
Highlights: Double layer gamma ray exposure buildup factors (DBUFs) for concrete, iron, lead, and tungsten. Comparative analysis of DBUFs using MCNP, ASFIT and empirical formulae. Modification of the correction factors of Kalos formula for the materials investigated. Radiation shielding experiments to validate MCNP computations. Standardization of modified Kalos formula. Abstract: Gamma ray exposure buildup factors (BUFs) are used in point kernel method based shielding codes to estimate the scattered radiation dose rate. BUFs computed by assuming single material for multi-layer shielding configuration either overestimate or underestimate the dose rates. Hence, BUFs computed based on stratified shielding configuration give better estimates of scattered dose rate and provide scope for further optimization of shielding thickness. In nuclear and radiological facilities, shielding materials such as concrete (Con), iron (Fe), lead (Pb), and tungsten (W) are normally used as single or multi-layer shields. For the first time, buildup factors estimated based on Monte Carlo simulations (MCS) for double layer shielding configurations (DBUFs) of W and Fe, W and Con, Pb and Fe, Pb and Con, and Fe and Con are reported. The estimated DBUFs are compared with the values obtained using the empirical formulae published by several authors. A significant variation up to 40% is observed between MCS and empirical formulae. Hence, the correction factor in the empirical formula of Kalos' is modified and standardized by carrying out further computations for various double layer shielding configurations and energies. Radiation shielding experiments performed to validate the MCS results are presented.